The fountain of knowledge : the role of universities in economic development - Breznitz, Shiri M. (Innovation and technology in the world economy., 2014)
This study analyzes two world-renowned universities - Yale and Cambridge - their investment in technology commercialization, and the outcome of this contribution in their local economies. This book has three main arguments: the way in which a university goes about improving its technology-transfer capability matters; by choosing a particular path of change, the university also changes its role and its ability to contribute to the region; and not all changes will positively affect the local economy.